Analisis Sistem Antrian Dalam Meningkatkan Efektifitas Pelayanan Pasien Rawat Jalan Di Rumah Sakit Prasetya Bunda - Muhamad Edwin Juwana; Suci Putri Lestari; Barin Barlian (Global Leadership Organizational Research in Management, 2024)
The increasing public demand for daily service needs has led to intense competition in today's business world. For service companies, an optimal service system is their main weapon in competing effectively. Service effectiveness is crucial in gaining positive customer ratings. However, the high demand for the service sector results in the number of customers continuing to increase while the number of service providers remains limited. This research aims to optimize the service system by utilizing the multi-channel multi-phase queuing model. This model allows for multiple service facilities to be available to serve incoming customers. In this study, the queuing model formula (M/M/1) & (M/M/2) was used to analyze the single channel- single phase and multi-channel- multi phase queuing systems. The results show that the patient arrival rate is smaller than the patient service rate, which indicates a good level of effectiveness in the single channel-single phase queuing system. However, by adding one server to be able to implement the multi channel - multi phase queuing model, the effectiveness of the queuing system can be improved. This research provides a better understanding of the importance of service effectiveness in the face of increasing demand. By using the right queuing model and adding servers, service companies can improve service efficiency.